2008
DOI: 10.1200/jco.2008.16.1547
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose Escalation and Pharmacokinetic Study of BI 2536, a Novel Polo-Like Kinase 1 Inhibitor, in Patients With Advanced Solid Tumors

Abstract: The MTD of BI 2536 when administered as a single-dose, 1-hour infusion was 200 mg; BI 2536 was well tolerated and showed a favorable pharmacokinetic profile. Antitumor activity of BI 2536 was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 20 publications
8
138
3
Order By: Relevance
“…However, delayed toxicity, manifest as a drastic decrease in peripheral WBCs, was evident within 24-36 h after free drug administration. This type of toxicity was identical to that observed in human clinical trials (53)(54)(55). Although toxic to bone marrow, the free BI-2536 was able to induce a significant antitumor response, slowing tumor growth by ∼30% after two doses at its maximum tolerated dose (MTD) (Fig.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hysupporting
confidence: 75%
See 1 more Smart Citation
“…However, delayed toxicity, manifest as a drastic decrease in peripheral WBCs, was evident within 24-36 h after free drug administration. This type of toxicity was identical to that observed in human clinical trials (53)(54)(55). Although toxic to bone marrow, the free BI-2536 was able to induce a significant antitumor response, slowing tumor growth by ∼30% after two doses at its maximum tolerated dose (MTD) (Fig.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hysupporting
confidence: 75%
“…It has been shown that BI-2536 has potent tumoricidal activity against cancer cells, particularly those harboring mutations in TP53 (44-47). BI-2536 was the subject of several clinical trials in patients with cancers of the lung, breast, ovaries, and uterus (48)(49)(50)(51)(52)(53). Although it showed evidence of efficacy in cancer patients, its development was abandoned after phase II trials revealed unacceptable toxicity (grade 4 neutropenia) at subtherapeutic doses.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hymentioning
confidence: 99%
“…Whether this was because of inadequate concentrations of Nutlin-3 in vivo for prolonged periods is not known. On the other hand, the major toxicity of BI-2536 in Phase I trials has been hematopoietic, with dangerous levels of neutropenia observed after treatment with this agent in the majority of patients (51). To determine whether Nutlin-3 could rescue this toxicity, we administered the combination of oral Nutlin-3 (200 mg/kg) and BI-2536 (100 mg/kg) to BALB/c mice.…”
Section: Transcriptional Profile Of Cells With and Without Wt Tp53mentioning
confidence: 99%
“…BI 2536, 46 BI 6727 47 and GSK461364 48 showed antitumor activity and stabilized disease in a subset of patients with advanced solid tumors, with manageable and reversible toxicity. Based on our results, it is plausible that PLK1-targeting drugs may also have therapeutic potential in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%